2020
DOI: 10.2147/dmso.s262950
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Insulin-Regulated FOXC2 Expression in Adipocyte Differentiation and Insulin Resistance</p>

Abstract: Objective 1) To investigate the effect of FOXC2 on the differentiation of adipose-derived mesenchymal stem cells. 2) To analyze the mechanism between FOXC2 expression regulation in adipose differentiation and insulin resistance (IR). Methods We first amplified the FOXC2 promoter region-512 and cloned it into the luciferase expression vector. The reporter gene system was transfected into the adipose tissue-derived mesenchymal stem cell to study insulin-mediated FOXC2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our previous research has confirmed that FOXC2 is strongly associated with glycolipid metabolism [10,11]. The polymorphism of C-512T in the 5 untranslated region of FOXC2 is significantly associated with insulin resistance (HOMA-IR) [12].…”
Section: Introductionmentioning
confidence: 72%
“…Our previous research has confirmed that FOXC2 is strongly associated with glycolipid metabolism [10,11]. The polymorphism of C-512T in the 5 untranslated region of FOXC2 is significantly associated with insulin resistance (HOMA-IR) [12].…”
Section: Introductionmentioning
confidence: 72%
“…Forkhead box C2 (FOXC2) is an important member of helix/forkhead transcription factor family 19 , and plays an important role in regulating lipid metabolism and glucose metabolism 20 . Therefore, FOXC2 was considered to have the function to regulate insulin resistance 21 . More importantly, Nian et al 22 showed that FOXC2 expression in visceral adipose tissue of type 2 diabetes patients was significantly lower than those of non-diabetes patients.…”
Section: Introductionmentioning
confidence: 99%